Theoretical and experimental evaluation of the distance dependence of fiber-based fluorescence and reflection measurements for laser lithotripsy. (1st September 2022) - Lange, Birgit; Ozimek, Tomasz; Wießmeyer, Judith Riccarda; Kramer, Mario W; Merseburger, Axel S; Brinkmann, Ralf
Abstract: Objectives . In laser lithotripsy, a green aiming beam overlying the infrared (IR) treatment radiation gives rise to reflection and fluorescence signals that can be measured via the treatment fiber. While stone autofluorescence is used for target detection, the condition of the fiber can be assessed based on its Fresnel reflection. For good applicability, fluorescence detection of stones should work even when the stone and fiber are not in direct contact. Fiber breakage detection, on the other hand, can be falsified if surfaces located in front of the fiber reflect light from the aiming laser back into it. For both applications, therefore, a fundamental investigation of the dependence of the signal amplitude on the distance between fiber and surface is important. Methods . Calculations of the signal drop of fluorescence or diffuse and specular reflection with increasing fiber distance were performed using ray tracing based on a simple geometric model for different fiber core diameters. Reflection signals from a mirror, diffuse reflector, human calculi, and porcine renal tissue placed in water were measured at varying distances (0–5 mm). For human calculi, fluorescence signals were recorded simultaneously. Results . The calculations showed a linear signal decrease down to ∼60% of the maximum signal (fiber in contact). The distance z at which the signal drops to for example 50% depends linearly on the diameter of the fiber core. For fibers used in lithotripsy and positioned in water, z 50% ranges from 0.55 mm (200 μ m core diameter) to 2.73 mm, (1 mm core diameter). The calculations were in good agreement with the experimental results. Conclusions . The autofluorescence signals of stones can be measured in non-contact mode. Evaluating the Fresnel signal of the end face of the fiber to detect breakage is possible unless the fiber is situated less than some millimeters to reflecting surfaces.